National Systems of Higher Education: The U21 Rankings - Williams, Ross (International Higher Education, 2016)
It is the quality of the higher education system as a whole, not just that of research intensive universities, that matters for the economic, social and cultural development of a nation. The annual Universitas 21 (U21) rankings measure national performance in higher education in 50 countries over 25 attributes. The relationship between the input and output measures enables conclusions to be drawn about the efficacy of different systems.